656 Self-isolation due to COVID-19 was not associated with changes in depression, sleepiness, and insomnia in Shiga prefecture, Japan. (3rd May 2021) - Kadotani, Hiroshi; Ubara, Ayaka; Sumi, Yukiyoshi; Ito, Kazuki; Matsuda, Arichika; Miyamoto, Towa; Omichi, Chie
Abstract: Introduction: We aimed to analyze the changes in depression, sleepiness, insomnia, and sleep habits in relation to the degree of self-isolation due to COVID-19 pandemic. A state of emergency was declared for the whole of Japan on 7 April 2020. People in Shiga prefecture were recommended to stay at home and refrain from moving to other prefectures from 8 April to 31 May 2020. Methods: We enrolled 54 patients who regularly visited the sleep outpatient clinic in Shiga University of Medical Science Hospital, Japan. We compared the sleep habits, depression (Patient Health Questionnaire-9: PHQ-9), insomnia (Athens Insomnia Scale: AIS), and sleepiness (Epworth Sleepiness Scale: ESS) of patients, one year before (from April to July 2019), during (May 2020) and six months after (Nov 2020) the self-isolation period due to the COVID-19. We conducted repeated measures ANOVA to examine changes. Results: PHQ-9 (3.89±0.64, 3.65±0.62 and 3.52±0.66: p=0.410), AIS (4.78±0.59, 4.65±0.57 and 4.63±0.57: p=0.843) and ESS (7.93±0.76, 7.07±0.68 and 7.00±0.73: p=0.088) were not significantly different among three visits. Sleep duration (6.06±0.23hr, 6.29±0.19hr and 6.16±0.22hr: p=0.248) and sleep onset latency (24.8±5.55min, 19.2±3.97min and 21.0±4.85min: p=0.445) were also not significantly different. Conclusion: Self-isolation due to COVID-19 was not associated with changes in depression, sleepiness, and insomnia among patients for sleep outpatient units in in Shiga prefecture, Japan. Support (if any): The present study was supported by MEXT/JSPS (KAKENHI Grant Number: 17H00872).